Schengen, Dublin und Maastricht: Etappen auf dem Weg zu einer europäischen Immigrationspolitik - Johannes Velling (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
With the fall of the borders between (most of) the countries of the Common Market, the member countries of the EC have lost one of their most important instrument to control immigration: the control of their external borders. This fact combined with the increasing immigration pressure from outside forced most EC members to think of a common European migration policy. Thus, as the idea of the 'market without borders' materialized, some EC countries started to make first contractual arrangements to mitigate the negative effects of lifting the borders between them. The paper discusses the international treaties relevant for a European immigration policy which have been decided upon so far and tries to evaluate the consequences and the reasoning of the recent developments. The discussion takes place based on a framework for a migration policy which is developed in the first part.
Keywords: 330; Migrationspolitik; EU-Staaten